Social and Cognitive Impressions of Adults Who Do and Do Not Stutter Based on Listeners' Perceptions of Read-Speech Samples - Amick, Lauren J.; Chang, Soo-Eun; Wade, Juli; McAuley, J. Devin (Frontiers in Psychology, 2017)
Stuttering is a neurodevelopmental disorder characterized by frequent and involuntary disruptions during speech production. Adults who stutter are often subject to negative perceptions. The present study examined whether negative social and cognitive impressions are formed when listening to speech, even without any knowledge about the speaker. Two experiments were conducted in which naïve participants were asked to listen to and provide ratings on samples of read speech produced by adults who stutter and typically-speaking adults without knowledge about the individuals who produced the speech. In both experiments, listeners rated speaker cognitive ability, likeability, anxiety, as well as a number of speech characteristics that included fluency, naturalness, intelligibility, the likelihood the speaker had a speech-and-language disorder (Experiment 1 only), rate and volume (both Experiments 1 and 2). The speech of adults who stutter was perceived to be less fluent, natural, intelligible, and to be slower and louder than the speech of typical adults. Adults who stutter were also perceived to have lower cognitive ability, to be less likeable and to be more anxious than the typical adult speakers. Relations between speech characteristics and social and cognitive impressions were found, independent of whether or not the speaker stuttered (i.e., they were found for both adults who stutter and typically-speaking adults) and did not depend on being cued that some of the speakers may have had a speech-language impairment.